Creative teaching in English language classrooms: A reflective and contextual interpretation - Ahsanu, Muhamad; Wardani, Erna; Ashari, Ashari (JEES (Journal of English Educators Society), 2025)
Creativity has become a defining competency in twenty-first-century higher education, particularly in English language teaching (ELT), yet how university educators conceptualize and enact it remains under-explored. This study investigates the lived experiences of two Indonesian lecturers—one from a public and one from a private university—through a narrative inquiry approach supported by classroom observations and thematic analysis. The findings reveal that creative teaching in ELT is a reflective, adaptive, and contextually grounded process characterized by continual negotiation between pedagogical innovation and institutional constraints. Two interrelated models emerged: the Five-Facet Framework (FFF) (teaching capital, material, media, method, and evaluation) and Reflective Adaptation as the sustaining mechanism of creativity. Effective creative teaching was found to rely not on isolated techniques but on the orchestration of these five components, harmonized like instruments in an orchestra. Teachers’ passion, autonomy, and responsiveness to learners’ needs serve as catalysts that transform routine instruction into dynamic, student-centered learning experiences. Reflection and contextual empowerment further enable resilience amid limited resources and rigid curricula. The study contributes to sociocultural and constructivist perspectives by framing creativity as both a personal and collective endeavour—rooted in interaction, reflection, and contextual engagement. Theoretically, it reaffirms that creative teaching forms the foundation of effective pedagogy; practically, it advocates institutional support systems that nurture reflective professional cultures and empower teachers to sustain innovation in ELT.